Les créoles louisianais défendent la cause du Sud à Paris (1861‑1865) - Salwa Nacouzi (Transatlantica)
During the Civil war, the French‑educated Creole elite of Louisiana played an important part in efforts to persuade France to support the Confederacy. This article analyses the arguments put forward by three famous Creoles living in Paris during the Civil War (Paul Pequet du Bellet, Dr Alfred Mercier and Dr Charles Delèry) to rally French public opinion to the cause of the Confederacy. Faced with a strong anti‑slavery sentiment, they argued that France’s interest lies in defending the South and its « Latin race » from the aggressions of the Anglo‑Saxon North.